Luke's Literary Achievement : Collected Essays. - Tuckett, Christopher M. (Library of New Testament studies., 1995)
The essays in this collection come from a research symposium involving the universities of Manchester and Lausanne. The essays cover a wide range of mutually-enriching approaches to the study of the Lukan writings. Aspects considered include Luke's use of the term 'Son of Man', his use of scripture, his literary achievements, and the issue of 'godfearers' in Acts.